Changes in psychological well-being after disclosing negative autobiographical memories - Mert, Nazike. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Emotional disclosure of negative experiences has long been associated with improvement in physical and psychological health (Pennebaker, 1997). The present study has three main goals: First, to test whether disclosure of previously undisclosed autobiographical memories (AMs) is more beneficial than disclosed memories. Second, to find whether disclosing shame and guilt memories differs in terms of health consequences. Third, to determine the predictors of well-being. To achieve these goals, participants were randomly assigned to three groups: undisclosed shame, guilt or disclosed negative memory, and attended three writing sessions. Well-being measures were collected before, immediately after writing and one month after the writing sessions. Results revealed that, contrary to our hypotheses, immediate psychological and physical symptoms decreased through writing sessions. However, in long term psychological and physical health deteriorated. Shame and guilt memories did not show any difference, but undisclosed memory groups were affected more negatively by emotional disclosure than disclosed memory group. Finally, negative affect and resolution were found to be significant predictors of well-being. Overall, the present study failed to replicate previous studies with shame and guilt memories. Moreover, the reverse effect demonstrated that benefits of emotional disclosure might be more restricted to certain types of memories and health outcomes.
Keywords: Autobiographical memory.